THE HIGH-PERFORMANCE RESOURCE-SPARING TECHNOLOGIES IN THE DIAGNOSTIC MAMMOLOGY (On the fifth anniversary of the Russian association of mammologists) - N. I. Rozhkova (ABV-press, 2014)
There have been presented the main achievements in the field of mammologic service development in Russia owing to creation and introduction of the domestic mammographic stationary digital and mobile mammographs, organization of the system of the continuous education of the specialists on basis of interdisciplinary integration, as well as introduction of the novel technologies of the radiologi- cal examination, interventional radiology, molecular biology, informational technologies, realization of the wide-ranging information- al educational work. The diagnostic mammology development perspectives are outlined.